To understand and to challenge the politicization of migration and interculturality.Book review: Sandoval-García, C. (Ed.) (2020). Bridges, Not Walls: Contributions for a progressive policy on migration. CLACSO. - Roldán-Soto, Sophia (2021)
The welfare state, richness distribution, sustainable development, human rights are some of the elements identified in progressists policies. Forced displaced people have been excluded from these elements. Carlos Sandoval García analyzes this exclusion in this book which is the result of the colloquium: "Migration Politicization. Challenges for critical thinking and progressists policies" published in 2017. This book collects the thoughts of 12 authors and is organized into eight chapters regarding the securitization of migration, racialization of class, symbols and identity building, political movements, nativism, and the emancipation of the Global South, especially in the Central American context.